Pengaruh Manajemen Waktu dan Motivasi Kerja terhadap Kinerja Pegawai Universitas Terbuka Cabang Pondok Cabe - Delia Maghfi Hanifah; Rony Edward Utama (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
Employee performance plays a crucial role in ensuring organizational effectiveness, particularly in higher education institutions that implement distance learning systems. In practice, employee performance is often influenced by both technical and psychological factors, such as time management and work motivation. However, empirical studies that examine these factors simultaneously within distance learning based universities remain limited. This study aims to analyze the effect of time management and work motivation on employee performance at the Pondok Cabe Branch of the Open University. This research employed a quantitative approach with an associative research design. The population consisted of all 50 employees at the Pondok Cabe Branch, and a saturated sampling technique was applied. Data were collected through structured questionnaires using a five-point Likert scale. The data were analyzed using multiple linear regression with the assistance of SPSS software. The findings indicate that time management has a positive but statistically insignificant effect on employee performance. In contrast, work motivation shows a positive and significant effect on employee performance. Simultaneously, time management and work motivation jointly influence employee performance. These results suggest that work motivation is a more dominant factor in enhancing employee performance within a structured organizational system. The study provides practical insights for human resource management strategies in distance learning based higher education institutions.